2020
DOI: 10.1016/j.adro.2020.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Markerless Tumor Tracking Using the On-Board Imager of a Commercial Linear Accelerator Equipped With Fast-kV Switching Dual-Energy Imaging

Abstract: Purpose To describe and characterize fast-kV switching, dual-energy (DE) imaging implemented within the on-board imager of a commercial linear accelerator for markerless tumor tracking (MTT). Methods and Materials Fast-kV switching, DE imaging provides for rapid switching between programmed tube voltages (ie, 60 and 120 kVp) from one image frame to the next. To characterize this system, the weighting factor used for logarithmic subtraction and signal difference-to-noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 37 publications
(61 reference statements)
0
29
0
Order By: Relevance
“…The image quality is influenced by image acquisition parameters and patient related factors such as patient diameter, overlying structures and location and size of the tumor. To improve image quality, dual-energy systems are one technology being studied [19]. Tumor 1 was challenging to track mainly due to overprojection of the spine; in this case, tracking was possible for 55% of the time.…”
Section: Discussionmentioning
confidence: 99%
“…The image quality is influenced by image acquisition parameters and patient related factors such as patient diameter, overlying structures and location and size of the tumor. To improve image quality, dual-energy systems are one technology being studied [19]. Tumor 1 was challenging to track mainly due to overprojection of the spine; in this case, tracking was possible for 55% of the time.…”
Section: Discussionmentioning
confidence: 99%
“…The cancer detection rate, motion tracking error,and computer-aided localization of lung nodules could be improved with some commercially available softwares, such as OnGuard, SoftView, Clear-Read + Detect, [21][22][23][24] or the Samsung BS Software. 25 Block et al 20 and Roeske et al 26 tested RapidTrack software (Varian Medical Systems, Palo Alto, CA, USA) in a phantom and patient study and reported a decrease in tracking range error when BS images were used for image registration. Nodule detection visibility could also be improved with a combination of machine learning and pattern recognition algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Block et al 20 . and Roeske et al 26 . tested RapidTrack software (Varian Medical Systems, Palo Alto, CA, USA) in a phantom and patient study and reported a decrease in tracking range error when BS images were used for image registration.…”
Section: Introductionmentioning
confidence: 99%
“…4,[6][7][8][9][10] One of these approaches is dual-energy (DE) subtraction imaging that improves the contrast of lung tumors by removing bone and has been shown to increase the accuracy of MTT. [8][9][10][11][12][13] However, this improved tumor contrast comes at the cost of increased image noise, 13 which may decrease the accuracy of MTT. To regain the benefits of bone removal, several noise reduction techniques have been investigated for DE imaging primarily in the diagnostic setting.…”
Section: Introductionmentioning
confidence: 99%
“…Although several tracking approaches are being considered for MTT, we and others have been investigating the use of template tracking algorithms. 6,[9][10][11] Template tracking uses 2-D templates of the tumor generated from the planning CT scan at the corresponding imaging angle. The template is scanned within a defined search window and the normalized cross-correlation (NCC) is calculated between template and image.…”
Section: Introductionmentioning
confidence: 99%